Thermodynamic studies on removal of reactive blue 19 dye on cross-linked chitosan/oil palm ash composite beads - Masitah, Hassan; Bassim, H. H.; Abdul Latif, A. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/